Kinerja keuangan perusahaan: tinjuan analisis rasio likuiditas dan profitabilitas - Sularsih, Hermi; Junaidar Handayanto, Adrian; Himawan W, Sukarno; Ndelu Lembo, Helmina (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2023)
The aim of this research is to find out the financial performance of pharmaceutical companies listed on the Indonesia Stock Exchange for the 2020–2022 period in terms of liquidity and profitability. This research is quantitative research using an associative approach. The population used in this research is all pharmaceutical companies registered on the IDX. The sampling technique used in this research was purposive sampling. So the number of samples in this study was ten pharmaceutical companies listed on the IDX which were selected according to predetermined sampling criteria. Data collection in this research is documentation. Data analysis methods use descriptive statistics, multiple linear regression analysis, classical assumption testing, and hypothesis testing. Research findings show that liquidity and profitability have a positive and significant effect on the financial performance of pharmaceutical companies listed on the IDX. Profitability shows the company's potential to generate long-term income, while liquidity ensures that there is sufficient cash to carry out daily operations.